FAKTOR-FAKTOR YANG MEMENGARUHI KEBIJAKAN HUTANG - Wijaya, Emil Tanaga; Dewi, Sofia Prima (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research was conducted with the aim of obtaining empirical evidence regarding the effect of managerial ownership, firm size, institutional ownership, asset structure, and profitability on debt policy. The subject of this research is a manufacturing company that is consistently listed on the Indonesia Stock Exchange for the period 2018-2020. Sample selection using purposive sampling technique. Based on certain criteria obtained a sample of 44 manufacturing companies. This study uses secondary data that is processed using Eviews 12.0 software and hypothesis testing using multiple linear regression analysis. The results of this study indicate that firm size has a positive effect on debt policy, asset structure has a negative effect on debt policy, managerial ownership and profitability have no positive effect on debt policy, and institutional ownership has no negative effect on debt policy.